Machine vision - Zuech, Nello 1938- (Van Nostrand Reinhold, 1989)
Aimed at manufacturing managers and engineers looking for an introduction to computer vision and its potential, this book discusses the areas in which machine vision is being used, explains different types of machine vision hardware and software and summarizes research at several universities. The book's key chapter highlights the use of machine vision for automated inspections, discussing cases in bottling, parts, printed circuit board inspection and inspection and other areas. The authors explain how to pinpoint areas where machine vision can be applied effectively and the factors to consider. Included is a glossary of computer vision terms and a list of machine vision companies. This book should be of interest to manufacturing managers and engineers.